2008
DOI: 10.1017/s0007114508137898
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal biohydrogenation as affected by tanninsin vitro

Abstract: The aim of the present work was to study the effects of tannins from carob (CT; Ceratonia siliqua), acacia leaves (AT; Acacia cyanophylla) and quebracho (QT; Schinopsis lorentzii) on ruminal biohydrogenation in vitro. The tannins extracted from CT, AT and QT were incubated for 12 h in glass syringes in cow buffered ruminal fluid (BRF) with hay or hay plus concentrate as a substrate. Within each feed, three concentrations of tannins were used (0·0, 0·6 and 1·0 mg/ml BRF). The branched-chain volatile fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
141
4
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(174 citation statements)
references
References 41 publications
23
141
4
6
Order By: Relevance
“…The accumulation of RA in SAB from fermenters containing tannin feeds suggested that the linoleic acid isomerase activity (LA-I) was not affected by tannin addition. This result agrees with those reported by Vasta et al (2008), who showed that LA-I was unaffected by the inclusion of tannins during rumen in vitro incubations. In order to explain the RA accumulation through CE and QE after 12 and 18 h of incubation, respectively, the role of VA accumulation should be considered, inducing a negative feedback effect on the previous step of BH.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The accumulation of RA in SAB from fermenters containing tannin feeds suggested that the linoleic acid isomerase activity (LA-I) was not affected by tannin addition. This result agrees with those reported by Vasta et al (2008), who showed that LA-I was unaffected by the inclusion of tannins during rumen in vitro incubations. In order to explain the RA accumulation through CE and QE after 12 and 18 h of incubation, respectively, the role of VA accumulation should be considered, inducing a negative feedback effect on the previous step of BH.…”
Section: Discussionsupporting
confidence: 93%
“…The potential effects of tannins on rumen microflora are influenced by the molecular structure of these polyphenols (Min et al, 2003;Vasta et al, 2008 and. Hence, when the present study was planned, two different sources of tannins were selected: chestnut as a source of HT and quebracho as a source of CT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, iso-BCFA are synthesized by cellulolytic strains (the microorganisms mainly involved in ruminal BH; Kepler and Tove, 1967), consequently being considered valuable predictors of ruminal bacterial activity. Tanniferous compounds were reported to reduce considerably the concentration of iso-BCFA in the rumen (Vasta et al, 2009a(Vasta et al, , 2009b(Vasta et al, , 2010.…”
Section: " "mentioning
confidence: 99%